Peer review in an Era of Evaluation Understanding the Practice of Gatekeeping in Academia - Forsberg, Eva; Geschwind, Lars; Levander, Sara; Wermke, Wieland (Springer Nature, 2022)
This open access volume explores peer review in the scientific community and academia. While peer review is as old as modern science itself, recent changes in the evaluation culture of higher education systems have increased the use of peer review, and its purposes, forms and functions have become more diversified. This book put together a comprehensive set of conceptual and empirical contributions on various peer review practices with relevance for the scientific community and higher education institutions worldwide. Consisting of three parts, the editors and contributors examine the history, problems and developments of peer review, as well as the specificities of various peer review practices. In doing so, this book gives an overview on and examine peer review , and asks how it can move forward. This is an open access book.